Seasonal and annual variation of carbon exchange in an evergreen Mediterranean forest in southern France - ALLARD, V; Ourcival, J M; Rambal, S; Joffre, R; Rocheteau, A (Global Change Biology, 2008)
We present 9 years of eddy covariance measurements made over an evergreen Mediterranean forest in southern France. The goal of this study was to quantify the different components of the carbon (C) cycle, gross primary production (GPP) and ecosystem respiration (Reco), and to assess the effects of climatic variables on these fluxes and on the net ecosystem exchange of carbon dioxide. The Puéchabon forest acted as a net C sink of −254 g C m−2 yr−1, with a GPP of 1275 g C m−2 yr−1 and a Reco of 1021 g C m−2 yr−1. On average, 83% of the net annual C sink occurred between March and June. The effects of exceptional events such the insect-induced partial canopy defoliation that occurred in spring 2005, and the spring droughts of 2005 and 2006 are discussed. A high interannual variability of ecosystem C fluxes during summer and autumn was observed but the resulting effect on the annual net C budget was moderate. Increased severity and/or duration of summer drought under climate change do not appear to have the potential to negatively impact the average C budget of this ecosystem. On the contrary, factors affecting ecosystem functioning (drought and/or defoliation) during March–June period may reduce dramatically the annual C balance of evergreen Mediterranean forests.
Keywords: CO2 fluxes; eddy covariance; Mediterranean ecosystem; Quercus ilex